Hera : queen of the gods, goddess of marriage - Temple, Teri.; Squier, Robert (Mankato, MN : Child's World, 2013)
An introduction to Greek mythology that shares the stories and myths about the Greek goddess Hera, queen of the gods and goddess of marriage.
Includes bibliographical references (p. 32) and index.
Library Media Connection
Library Media Connection, May 2013
4.0
3-6.
3-6
Keywords: Hera (Greek deity) -- Juvenile literature; Mythology, Greek -- Juvenile literature; Hera (Greek deity); Mythology, Greek; Greek mythology; Hera (Greek deity)